Soil carbon under current and improved land management in Kenya, Ethiopia and India: Dynamics and sequestration potentials - Sommer, Rolf; Silva, Mayesse Aparecida da; Nyawira, Sylvia; Abera, Wuletawu; Tamene, Lulseged D.; Yaekob, Tesfaye; Kihara, Job Maguta; Piikki, Kristin; Söderström, Mats; Margenot, Andrew J. (2018)
Agriculture is a major contributor to climate change, emitting the three major greenhouse gases (GHGs) – carbon dioxide (CO2), methane and nitrous oxide – into the atmosphere. According to the Fifth Assessment Report of the Intergovernmental Panel on Climate Change (IPCC), the Agriculture, Forestry and Other Land Use sector “is responsible for just under a quarter (~10–12 Gt CO2eq/yr) of [all] anthropogenic GHG emissions mainly from deforestation and agricultural emissions from livestock, soil and nutrient management”. Land use change – often associated with deforestation – contributes about 11.2% to this share, while agricultural production is responsible for 11.8% (IPCC, 2014). To reduce emissions from agriculture, while providing and maintaining global food security, there is a growing interest to develop and promote low-emission greengrowth pathways for future agricultural production systems. Sub-Saharan Africa (SSA) faces two concerns in that respect: a) agriculture is the major emitter of GHGs on this sub-continent, and b) agriculture is largely underperforming. To feed a growing population, productivity and total production need to increase significantly. To achieve this while reducing emissions from agriculture at the same time is a major challenge. Climate-smart agriculture (CSA) sets out to address this challenge by transforming agricultural systems affected by the vagaries of climate change. CSA aims at improving food security and system’s resilience while addressing climate change mitigation.